Sustainable Practice of Sukuk - Ataollah Rahmani; Dandy Okorontah (Profetika: Jurnal Studi Islam, 2025)
Objective: This study aims to analyze the current sukuk practices and formulate strategies to increase sustainability in sukuk transactions. The main focus of the research is to bridge the gap between sustainability principles and Islamic financial practices, particularly in sukuk transactions, to maximize their contribution to the Sustainable Development Goals (SDGs). Theoretical framework: Based on sharia principles and sustainable finance theory, especially ESG aspects in Sukuk instruments. Literature review:  There is a considerable amount of sukuk literature, but studies on its relationship with sustainability and ESG are still limited and in-depth. Methods: Using qualitative methods through the analysis of literature and Islamic financial sector sources to evaluate the suitability of sukuk with sustainability principles. Results: The results show that sukuk has great potential as an innovative financial instrument that can directly support the Sustainable Development Goals (SDGs), including access to affordable renewable energy, infrastructure development, and the creation of sustainable cities and communities. Implications: Provides a basis for academics and policymakers to develop a sustainable sukuk policy framework. Novelty: Offers a new approach that explicitly links sukuk and ESG, as well as practical strategies for its integration in Islamic finance.